Morphologic and Molecular Characterization of Adrenals and Adrenal Rest Affected by Congenital Adrenal Hyperplasia - Kolli, Vipula; da Cunha, Isabela Werneck; Kim, SunA; Iben, James R.; Mallappa, Ashwini; Li, Tianwei; Gaynor, Alison; Coon, Steven L.; Quezado, Martha M.; Merke, Deborah P. (Frontiers in Endocrinology, 2021)
Introduction: Adrenocortical hyperplasia and adrenal rest tumor (ART) formation are common in congenital adrenal hyperplasia (CAH). Although driven by excessive corticotropin, much is unknown regarding the morphology and transformation of these tissues. Our study objective was to characterize CAH-affected adrenals and ART and compare with control adrenal and gonadal tissues. Patients/Methods: CAH adrenals, ART and control tissues were analyzed by histology, immunohistochemistry, and transcriptome sequencing. We investigated protein expression of the ACTH receptor (MC2R), -steroidogenic ( CYP11B2, CYP11B1, CYB5A) and immune (CD20, CD3, CD68) biomarkers, and delta-like 1 homolog (DLK1),a membrane bound protein broadly expressed in fetal and many endocrine cells. RNA was isolated and gene expression was analyzed by RNA sequencing (RNA-seq) followed by principle component, and unsupervised clustering analyses. Results: Based on immunohistochemistry, CAH adrenals and ART demonstrated increased zona reticularis (ZR)- like CYB5A expression, compared to CYP11B1, and CYP11B2, markers of zona fasciculata and zona glomerulosa respectively. CYP11B2 was mostly absent in CAH adrenals and absent in ART. .DLK1 was present in CAH adrenal, ART, and also control adrenal and testis, but was absent in control ovary. Increased expression of adrenocortical marker MC2R, was observed in CAH adrenals compared to control adrenal. Unlike control tissues, significant nodular lymphocytic infiltration was observed in CAH adrenals and ART, with CD20 (B-cell), CD3 (T-cell) and CD68 (macrophage/monocyte) markers of inflammation.. RNA-seq data revealed co-expression of adrenal MC2R, and testis-specific INSL3, HSD17B3 in testicular ART indicating the presence of both gonadal and adrenal features and high expression of DLK1 in ART, CAH adrenals and control adrenal. Principal component analysis indicated that the ART transcriptome was more similar to CAH adrenals and least similar to control testis tissue. Conclusions: CAH-affected adrenal glands and ART have similar expression profiles and morphology, demonstrating increased CYB5A with ZR characteristics and lymphocytic infiltration, suggesting common origin that is similarly affected by the abnormal hormonal milieu. Immune system modulators may play a role in tumor formation of CAH.